2007
DOI: 10.1007/s00264-007-0409-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of range of motion after standard and high-flexion posterior stabilised total knee replacement

Abstract: The purpose of this study was to compare the range of motion after standard version posterior stabilised TKR and high-flexion version TKR in patients receiving bilateral total knee replacement. Thirty-five patients were recruited. The range of motion of the knees was measured clinically with a goniometer in both the pre-operative period and the most recent follow-up. It was found that the preoperative range of motion was comparable in the two groups. The average post-operative flexion was 105°±13°in the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 13 publications
0
39
0
2
Order By: Relevance
“…Our study and five others in the literature [14,20,22,27,29] failed to prove an increase in flexion with the use of HF TKAs. However, there is evidence that suggests that HF TKA designs may improve intraoperative passive ROM and postoperative maximum weight-bearing flexion.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Our study and five others in the literature [14,20,22,27,29] failed to prove an increase in flexion with the use of HF TKAs. However, there is evidence that suggests that HF TKA designs may improve intraoperative passive ROM and postoperative maximum weight-bearing flexion.…”
Section: Discussionmentioning
confidence: 65%
“…In a systematic literature review focusing on outcomes after HF TKA, Murphy et al found that there was insufficient evidence to support the view that these new TKA designs improved ROM or functional performance [24]. This review included nine studies [1, 8,10,14,17,27,29,34,37] with 399 HF TKAs in 370 patients. They conclude that the claims of greater flexion, ROM, and function for HF TKA reported in some of those studies were not supported due to poor study designs, short follow-up periods, inadequate blinding, and use of functional outcome measures that lacked sensitivity [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoarthritis was the primary reason for TKA. Five of the nine studies were conducted in Asian populations reflecting the increased knee flexion demands in this region's cultural and religious activities [24][25][26][27][28].…”
Section: Literature Descriptionmentioning
confidence: 99%
“…A third study reported no difference in average postoperative knee flexion in 50 patients who underwent bilateral TKAs (138°for NexGen 1 LPS-Flex versus 135°for NexGen 1 LPS) [26]. To date, three of nine clinical studies suggest patients have increased postoperative flexion with highflexion prostheses [6,19,20,23,26,38,42,44,45]. One of these studies reported patients with maximum flexion greater than 135°had a better functional WOMAC Osteoarthritis Index score than patients with maximum flexion of 135°or less (17.5 versus 14.3) [45].…”
Section: Introductionmentioning
confidence: 99%